OPTIMIZATION OF TEACHER AND EMPLOYEE ATTENDANCE AT SMK MA'ARIF BANTARKAWUNG USING GENETIC ALGORITHM - Sudaryanto, Eko; Wahjudi, Dody; Darmawan, Isra' Nuur; Mauludin Sodik, Muhammad (Program Studi Teknik Elektro Universitas Peradaban, 2024)
A good company or agency has disciplined employees and good employee work scheduling. This is very much in line so that a company needs to create effective and appropriate employee work scheduling. SMK Ma'arif Bantarkawung itself still uses a manual system for employee scheduling. The purpose of writing this thesis is to increase knowledge to readers about genetic algorithms and teacher employee attendance using fingerprints. This algorithm works through several stages, initialization, reproduction, evaluation, selection. At the selection stage, individuals who have better traits will be selected to produce the next generation that is also better. According to several studies, scheduling is the process of scheduling the process of organizing, selecting, and determining the time of use of existing resources to produce the expected output within the expected time. The conclusion that can be drawn is the development of a schedule maker feature system, where school managers must enter the name, teacher code, hours, and subjects taught. Change schedule feature, where data managers only need to change data if they change semesters and subject teachers clash. Change data feature, where data managers only need to change data if subject teachers clash. The results of optimizing the absence of teachers of SMK Ma'arif Bantarkawung employees using genetic algorithms show that the scheduling of teacher absences of SMK Ma'arif Bantarkawung employees aims to create a schedule automatically, displaying the day and time on the teacher's schedule. This genetic algorithm completes the scheduling optimally, so that there is little schedule mismatch.